Carbonic Anhydrase 9 mRNA/microRNA34a Interplay in Hypoxic Human Mammospheres. Issue 7 (30th November 2015) - De Carolis, Sabrina; Bertoni, Sara; Nati, Marina; D'Anello, Laura; Papi, Alessio; Tesei, Anna; Cricca, Monica; Bonafé, Massimiliano
Abstract : The hypoxic environment is a crucial component of the cancer stem cell niche and it is capable of eliciting stem cell features in cancer cells. We previously reported that SNAI2 up‐regulates the expression of Carbonic Anhydrase iso‐enzyme 9 ( CA9 ) in hypoxic MCF7 cells. Here we show that SNAI2 down‐regulates miR34a expression in hypoxic MCF7 cell‐derived mammospheres. Next, we report on the capability of miR34a to decrease CA9 mRNA stability and CA9 protein expression. We also convey that the over‐expression of cloned CA9 ‐mRNA‐3′UTR increases the mRNA half‐life and protein levels of two miR34a targets JAGGED1 and NOTCH3 . The data here reported shows that the SNAI2‐dependent down‐regulation of miR34a substantially contributes to the post‐transcriptional up‐regulation of CA9, and that CA9 ‐mRNA‐3′UTR acts as an endogenous microRNA sponge. We conclude that CA9/miR34 interplay shares in the hypoxic regulation of mammospheres and therefore, may play a relevant role in the hypoxic breast cancer stem cell niche. J. Cell. Physiol. 231: 1534–1541, 2016. © 2015 Wiley Periodicals, Inc.